2022
DOI: 10.1007/s12144-021-02687-3
|View full text |Cite
|
Sign up to set email alerts
|

Burnout across boundaries: Can parental burnout directly or indirectly influence work outcomes?

Abstract: Burnout, while historically considered a work-related condition, can be associated with parenting where it can have direct impacts upon parental outcomes and one’s personal resources such as mental health. However, little is known about the domain-incongruent effects of burnout and thus whether parental burnout can manifest within the workplace. The current study uses longitudinal data collected from 499 parents over three intervals across an 8-month period to explore two possible mechanisms. Firstly, a direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 50 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have shown that parents of autistic children will experience more parental burnout, especially when children have a combination of physical and mental disabilities ( Gérain and Zech, 2018 ; Kütük et al, 2021 ). Chronic parental burnout can affect parents’ physical and mental health, such as increased cortisol, insomnia, overeating, and anxiety, which can decrease their work efficiency ( Brianda et al, 2020 ; Evans et al, 2022 ; Hormozi et al, 2022 ; Exhausted Parents in Japan, n.d. ). Some parents may even resort to alcohol or suicide to avoid parental responsibilities ( Mikolajczak et al, 2019 , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that parents of autistic children will experience more parental burnout, especially when children have a combination of physical and mental disabilities ( Gérain and Zech, 2018 ; Kütük et al, 2021 ). Chronic parental burnout can affect parents’ physical and mental health, such as increased cortisol, insomnia, overeating, and anxiety, which can decrease their work efficiency ( Brianda et al, 2020 ; Evans et al, 2022 ; Hormozi et al, 2022 ; Exhausted Parents in Japan, n.d. ). Some parents may even resort to alcohol or suicide to avoid parental responsibilities ( Mikolajczak et al, 2019 , 2021 ).…”
Section: Introductionmentioning
confidence: 99%